Android-based virtual laboratory with starter experiment approach for learning vertebrate organ systems in high school - Hasanah, Alfinatul; Risnasari, Medika (Jurnal Inovasi Teknologi Pendidikan, 2025)
Limited laboratory equipment causes practicum of vertebrate animal organ systems to be rarely carried out so that learning is only theoretical and has an impact on student understanding that is less than optimal. This study aims to develop and test the validity and feasibility of an Android-based virtual laboratory with a starter experiment approach on vertebrate animal organ system material for high schools. This media is also equipped with LKP (Practicum Worksheet) to support virtual laboratory activities. This research uses the Research and Development (R&D) method with the ADDIE model. Data were collected through validation questionnaires from media experts, material experts, and trials to students, then analyzed descriptively, quantitatively, and qualitatively. The validation results show that the virtual laboratory has a validity level of 91% from media experts and 89% from material experts, which is included in the "very valid" category. Meanwhile, the feasibility test results showed a value of 91% in individual trials, 96% in small groups, and 94% in large groups, all of which were included in the "very feasible" category. Thus, the Android-based virtual laboratory with a starter experiment approach on vertebrate animal organ system material is very valid and feasible to use in learning. This media helps teachers deliver material, enhances student understanding, and addresses lab limitations in technology-based learning. Further development should optimize app size for low-spec devices, ensure compatibility with iOS, and improve interactive features for a more realistic practicum experience.